2007
DOI: 10.1159/000100880
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of the Th1 Promoter IL-12 and the Th2 Chemokine TARC Are Elevated in Erythema Multiforme and Stevens-Johnson Syndrome/Toxic Epidermal Necrolysis and Correlate with Soluble Fas Ligand Expression

Abstract: Background: No data exist as to Th2 chemokines in erythema multiforme (EM) and Stevens-Johnson syndrome (SJS)/toxic epidermal necrolysis (TEN). Objective: To evaluate thymus- and activation-regulated chemokine (TARC), macrophage-derived chemokine (MDC) and regulated upon activation, normal T-lymphocyte-expressed and secreted chemokine (RANTES) expression in EM and SJS/TEN and to correlate with the serum levels of the Th1 promoter interleukin (IL)-12 and soluble Fas ligand (sFasL). Materials and Methods: IL-12,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 103 publications
6
17
0
Order By: Relevance
“…Identified factors involved in pathophysiology of EM-lesions are perforin, thymus-and activation-regulated chemokine (TARC), IL-12 and soluble Fas -ligand among others. 6,7 Remarkable that our patient: 1) does not belong to the preferred age group of zoster-induced erythema multiforme and 2) no other case treated with brivudin has yet been described. This drug may me theoretically the inducing factor for EM, however the course of EM in our patient suggests a closer relationship to virus-induced immune alterations than to antiviral drug use.…”
Section: Discussionmentioning
confidence: 78%
“…Identified factors involved in pathophysiology of EM-lesions are perforin, thymus-and activation-regulated chemokine (TARC), IL-12 and soluble Fas -ligand among others. 6,7 Remarkable that our patient: 1) does not belong to the preferred age group of zoster-induced erythema multiforme and 2) no other case treated with brivudin has yet been described. This drug may me theoretically the inducing factor for EM, however the course of EM in our patient suggests a closer relationship to virus-induced immune alterations than to antiviral drug use.…”
Section: Discussionmentioning
confidence: 78%
“…Regarding diseases with mucosal involvement, although a different aetiological mechanism has been proposed for EM and SJS ⁄TEN, 21 drug-induced EM shares clinical and pathological features with SJS. 7,22,23 Patient classification was confirmed by unsupervised hierarchical clustering of more accurate data generated by qRT-PCR analysis of gene expression levels, which resulted in a similar dendrogram, containing two main clusters in which bullous reactions were again separated from nonbullous diseases. It is of note than the two DRESS patients were again clustered separately from the rest of the diseases in the nonbullous group.…”
Section: Discussionmentioning
confidence: 90%
“…It has been proposed that EM and SJS/TEN could represent 2 distinct nosological entities with specific clinicopathological and immunological features [7,8,9]. However, many authors still consider EM, SJS and TEN to be a single disease group with different degrees of clinical severity.…”
Section: Discussionmentioning
confidence: 99%
“…These authors found differences in the expression of interleukin 13, Fas, cytokines and chemokine receptors in the cutaneous lesions of patients with EM compared to those with SJS/TEN [15]. However, the serum levels of interleukin 12 and the chemokine TARC [9] as well as the expression of matrix metalloproteinases 2, 9 and 11 [16] were increased in both EM and SJS/TEN; no statistically significant differences existed between the two groups. The immunological background that characterizes EM and SJS/TEN is still poorly defined, and further studies are needed to clarify if EM and SJS/TEN are different diseases or are part of a single spectrum of skin disorders.…”
Section: Discussionmentioning
confidence: 99%